2018
DOI: 10.1111/bju.14147
|View full text |Cite
|
Sign up to set email alerts
|

Sitting time, physical activity and the risk of lower urinary tract symptoms: a cohort study

Abstract: Prolonged sitting time and low physical activity levels were positively associated with the development of LUTS in a large sample of middle-aged Korean men. This result supports the importance of both reducing sitting time and promoting physical activity for preventing LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Sedentary lifestyle (prolonged sitting and physical inactivity) can produce changes in the musculoskeletal and vascular milieu in the pelvis and lower extremity vasculature and these changes may cause LUTS. 25 In the current study, we found that development of LUTS were affected by age, BMI, number of child-births, delivery methods, and having UI during pregnancy and postpartum. It is known that the prevalence of developing LUTS increases with advancing age.…”
Section: Discussionmentioning
confidence: 50%
“…Sedentary lifestyle (prolonged sitting and physical inactivity) can produce changes in the musculoskeletal and vascular milieu in the pelvis and lower extremity vasculature and these changes may cause LUTS. 25 In the current study, we found that development of LUTS were affected by age, BMI, number of child-births, delivery methods, and having UI during pregnancy and postpartum. It is known that the prevalence of developing LUTS increases with advancing age.…”
Section: Discussionmentioning
confidence: 50%
“…De Nunzio et al reported that physical activity is a protective factor against LUTS in male patients. Another study reported that prolonged sitting time and low physical activity levels were positively associated with the development of LUTS in a large sample of middle‐aged Korean men . So the difference in LUTS between women with a mental job and a physical job in the present study was probably due to the different degrees of physical activity.…”
Section: Discussionmentioning
confidence: 51%
“…Another study reported that prolonged sitting time and low physical activity levels were positively associated with the development of LUTS in a large sample of middleaged Korean men. 31 So the difference in LUTS between women with a mental job and a physical job in the present study was probably due to the different degrees of physical activity. In the literature, it has been reported that pregnant women living in rural areas have a higher degree of physical activity (doing domestic work) than pregnant women living in urban areas, 32 and the differences between these two groups in LUTS in the present study may also be explained by the degree of physical activity.…”
Section: In the Literature Recent Studies Involving Large Populationmentioning
confidence: 58%
“…Accumulating evidence suggests that modifiable metabolic and lifestyle factors are important in the etiology of BPH and LUTS including obesity, diabetes, diet and physical activity (Mongiu & McVary, 2009; Parsons et al, 2013; Raheem & Parsons, 2014). Physical activity of various intensities, including walking, has been reported not only to reduce BPH risk (Parsons & Kashefi, 2008; Platz et al, 1998), but also to delay its diagnosis and improve LUTS management (Park, Park, Chang, & Ryu, 2018; Wolin et al, 2015), presumably by decreasing autonomic nervous system over activation (Platz et al, 1998) and/or improving cardiovascular health (Parsons & Kashefi, 2008).…”
mentioning
confidence: 99%